Influence of Type of School (Special or General) on the Achievement of Students with Special Educational Needs - Romero Contreras, Silvia (Pontificia Universidad Javeriana, 2018)
In Mexico, children with special educational needs may be educated in integrative general schools or special education schools (Multiple Care Centers). In general, these services promote and support the process of educational integration. However, there is little evidence of the potential influence they have on student achievement. The present study evaluated the influence of the type of school in 23 children with special educational needs, 12 from regular school and 11 from Multiple Care Centers. Five academic achievement tests of Battery III Woodcock-Muñoz were applied. Results indicate a better overall performance and grade equivalents, more consistent with age, of integrating regular school students than of those in Multiple Care Centers, this was particularly the case for students who do not have a disability. However, according to grading standards, students' academic performance is generally very low.